(untitled) (Journal of Organizational Psychology, 2017)
This study is one of the first to empirically investigate how Turkish employees’ style of workplace dress affects their self-perceptions. Drawing on social identity theory, we predicted that different workplace attire styles would impact employee self-perceptions of creativity, friendliness, competence, trustworthiness, authority, and productivity in Turkey. Utilizing a sample of workers in a state-owned bank and two government agencies, we found that our respondents felt most authoritative, trustworthy, and competent when wearing formal business attire. In contrast, respondents felt least friendly and creative when wearing formal attire and this was true of all respondents, regardless of organizational dress norms.